Africa-Europe Research and Innovation Cooperation Global Challenges, Bi-regional Responses - Cherry, Andrew; Haselip, James; Ralphs, Gerard; Wagner, Isabella E. (Springer Nature, 2018)
Africa; EU; Cooperation; Policy; Partnership; Agriculture; Climate Change; Science; Development; Evidence-based policy; Networks; Funding; Engagement